NEOTRIBALISMO E NOVOS MOVIMENTOS RELIGIOSOS: ESTUDO DE CASO DA PRÁXIS DA IGREJA BOLA DE NEVE CHURCH - Araújo, Marcio Bergamo de (2006)
The present research Neotribalism and new religious movements: case study about the praxis of Igreja Bola de Neve Church is an in loco investigation that aims to analyse, describe and to interpret the context of an emerging religious praxis, with a theoric-scientifical approach of this religious movement. Since the 80s of the twentieth century a new social system emerged that allowed for the appearance of groups that create their own identity, especially in an urban context. One of those groups that arised were the so-called urban tribes. This neotribalist system, that allowed for the development of religious self-expression, is called New Religious Movements. One of the groups within this system draws attention: the Igreja Bola de Neve Church. The subject of this research has received a lot of attention from social and religious scientists, presenting itself as a new challenge for those studying practical theology, in trying to analyse the effects that this religious fenomenon has on contemporary society. The goal of this thesis is comprehending the theoric-scientific fundaments of the construction of the neotribalist social model and of the New Religious Movements. This research intends to investigate the creation of the Igreja Bola de Neve Church, describe it and interpret its religious practices based on the hermeneutics of the theory of religious praxis, in order to understand how the Igreja Bola de Neve Church is interpreted by christian religion.(AU)